MR diffusion tensor imaging applied to the spinal cord of patients with neuropathic pain secondary to herpes zoster infection - Yacubian Fernandes, Adriano [UNESP]; Fernandes da Silva, Fabio Eduardo; Hamamoto Filho, Pedro Tadao [UNESP]; Talamoni Fonoff, Erich (Elsevier, 2024)
Introduction: Diffusion tensor imaging (DTI) has been increasingly utilized in the assessment of spinal cord pathologies for various clinical applications. DTI surpasses conventional MRI in delineating the microstructural integrity of the spinal cord, thereby serving as a potent, non-invasive modality sensitive to white matter pathologies. Postherpetic neuralgia (PHN) is acknowledged to be a consequence not only of peripheral nerve and root lesions but also of central nervous system abnormalities associated with such damage. Our premise posits that the manifestation of PHN may be linked to detectable spinal cord anomalies ascertained through DTI methodologies. Material and methods: To study the spinal cord of the patients with post herpetic neuralgia (PHN) using DTI techniques, looking at the fractional anisotropy (FA) and apparent diffusion coefficient (ADC) to compare the parameters of the patients that developed PHN with the parameters of the patients that presented herpes zoster (HZ) but didn't present secondary neuralgia. Fifteen patients (two male and thirteen female) were studied. Ten patients presented PHN: nine female and one male; age from 54y to 83y (mean = 72,2). Five patients had HZ without chronic pain: four female and one male with age from 34y to 81y (mean = 60,8). Results: For ADC, we found higher values among the patients, significant differences in C5, T8, and T9 levels. For FA, we found lower values among the patients, significant differences in T7, T8, and T9 levels. On ROC curves, we identified that D8 was the single level with significant area under the curve (AUC) for discriminating patients with pain. For ADC, the AUC was 0.960 (95 %CI 0.865–1.000), p = 0.005. For FA, the AUC was 0.920 (95 %CI 0.764–1.000), p = 0.010. The cutoff value for pain on ADC was 2455.08, with a sensibility of 90 % and specificity of 100 %. For FA, the cutoff value for not having pain was 395.05, with sensibility of 100 %, and specificity of 90 %. Conclusion: This investigation highlights the potential for DTI parameters, specifically FA and ADC, to provide insight into the microstructural changes associated with PHN in patients following herpes zoster infection. Future research should continue to explore the implications of these findings in larger cohorts to further elucidate the pathogenesis of neuropathic pain in this population.
Keywords: Apparent Diffusion Coefficient; Diffusion Tensor Imaging; Fractional Anisotropy; Herpes Zoster; Postherpetic Neuralgia; Spinal Cord